Money Politics and Participation Awareness, Relevance to Moral Aqidah in Elections - Faizudin, Faizudin; Utang Ranuwijaya; Muhajir, Muhajir (al-Afkar, Journal For Islamic Studies, 2025)
Political awareness and public participation in general elections have a crucial role in maintaining democratic integrity and ensuring the success of democratic and representative elections. Political money, which uses funds or wealth for political gain, undermines aspects of honesty, fairness, and the legal system in elections. Solutions to overcome money politics involve qualitative methods, socialization and education involving political parties and community leaders. Moral aqidah in Islam also plays a role in dealing with the negative impact of political money, because aqidah values shape individual views on unethical political practices. Political education and socialization of moral aqidah values are the keys to forming a responsible character in elections. The regulations provided for in the law provide a basis for the prevention and prosecution of money politics offences. Collaboration involving political education, teaching moral values, an active role for political leaders, and strict law enforcement can reduce political money practices and strengthen the integrity of a clean, open and fair election system. Thus, overcoming money politics is not only about strengthening democracy, but also about maintaining moral values and moral beliefs in society.